Chemistry Motivation of High School Students in Indonesia: Grade Level and Gender Differences - Tsamara Salsabila; Suyanta; Nur Huda (Postgraduate, University of Mataram, 2023)
Chemistry motivation is one of the research topics that continues to grow today. This study aims to explore the chemistry learning motivation of high school students in Indonesia with a focus on differences based on gender and student grade. The research method used was a cross-sectional survey using an adapted questionnaire from the Chemistry Motivation Questionnaire II (CMQ II). The research sample consisted of 753 high school students from 9 schools in Yogyakarta and Bengkulu. The results of the validity and reliability analysis of the instrument showed that the CMQ II questionnaire used in this study was valid and reliable. The five dimensions of chemistry learning motivation measured through 25 question items are intrinsic motivation, self-efficacy, self-determination, career motivation, and grade motivation. The two-way ANOVA test was used to analyze significant differences in students' chemistry learning motivation based on gender and grade between populations. The results of quantitative data analysis also show that the interaction between gender and class has a significant difference with a significance level of 0.003, which means that there is a significant difference in students' chemistry motivation based on gender and class.